Character Education Values on Dialogue in English Textbook Entitle Bahasa Inggris Think Globally Act Locally - Alvionita, Sella; Arifmiboy, Arifmiboy (New Language Dimensions, 2020)
This research is aimed to find out 18 charatcter education values on dialogue in english textbook entitled œBahasa Inggris Think Globally Act Locally ninth grade on  semester one. Design of this research is descriptive qualitatif research.  The instrument of this research is observation sheet.  The data was collected from observation sheet to find out the 18 character education values in english textbook. The technique of data anlysis in this research is organizing and familiarizing, (2) coding and reducing or eliminating. The result of the research showed that all the 18 character values from the 2013 curriculum were already implemented in the book. It was found that there were 12 religiosity , 10 honesty, 3 tolerance, 2 hard work, only 1 creativity value, only 1 independent, only 1 value that was related with democracy, 7 examples that were related to the curiosity, only one nationalism and patriotism, were 27 appreciation values, 14 examples that were related to the friendship and communication, 15 sentences that were related with love of peace, 2 sentences that were related with fondness of reading, 3 sentences that were related with environmental awareness, 31 sentences that were related to the social care values, there were 3 sentences that were related with responsibility values.Key words : Textbook , 2013 curriculum, character education values